Roberta Vilka studenta karte - Latvijas Universitāte (My University, 1930)
Latvijas Universitātes Studentu padomes priekšsēdētāja (1934-1936), LU Tautsaimniecības un tiesību zinātņu fakultātes Tautsaimniecības nodaļas studenta (1924-1940) un latviešu studentu korporācijas Beveronija (1932) seniora Roberta Vilka studentu karte.

Student card of Robert Vilks, chairman of the Student Council of the University of Latvia (1934-1936), student of the Department of Economics at the Faculty of Economics and Law of the University of Latvia (1924-1940) and senior member of the Latvian Student fraternity Beveronija (1932).
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History; Latvijas Universitātes Studentu padome; Studentu akadēmiskās mūža organizācijas; Studentu korporācijas; Studentu dzīve; Student Council of the University of Latvia; Student academical lifetime organisations; Student fraternities; Student life